Tagetone Induces Changes in Lipid Composition of Panicum Miliaceum L. Roots - Zunino, María Paula (2005)
Terpenes are thought to be important in plant-plant interactions, because of their phytotoxic action on seed germination and growth. Despite of some efforts in studying the mode of action of terpenes at molecular level, little is known about their effect on plant lipid composition. Here, we demonstrate the ability of tagetone to inhibit the root growth of Panicum miliaceum L. seedlings, which was related with changes in sterols, alkanes and fatty acids composition. Some sterol and fatty acid ratios are discussed in relation to their function. The results suggest that tagetone exert their effect through impairing the structural and functional properties of root membrane.